A population of progenitor cells in the basal and intermediate layers of the murine bladder urothelium contributes to urothelial development and regeneration. Issue 8 (August 2014) - Colopy, Sara A.; Bjorling, Dale E.; Mulligan, William A.; Bushman, Wade
<x xml:space="preserve">Abstract</x> Background: Homeostatic maintenance and repair of the bladder urothelium has been attributed to proliferation of keratin 5‐expressing basal cells (K5‐BC) with subsequent differentiation into superficial cells. Recent evidence, however, suggests that the intermediate cell layer harbors a population of progenitor cells. We use label‐retaining cell (LRC) methodology in conjunction with a clinically relevant model of uropathogenic Escherichia coli (UPEC)‐induced injury to characterize urothelial ontogeny during development and in response to diffuse urothelial injury. Results: In the developing urothelium, proliferating cells were dispersed throughout the K5‐BC and intermediate cells layers, becoming progressively concentrated in the K5‐BC layer with age. When 5‐bromo‐2‐deoxyuridine (BrdU) was administered during urothelial development, LRCs in the adult were found within the K5‐BC, intermediate, and superficial cell layers, the location dependent upon time of labeling. UPEC inoculation resulted in loss of the superficial cell layer followed by robust proliferation of K5‐BCs and intermediate cells. LRCs within the K5‐BC and intermediate cell layers proliferated in response to injury. Conclusions: Urothelial development and regeneration following injury relies on proliferation of K5‐BC and intermediate cells. The existence and proliferation of LRCs within both the K5‐BC and intermediate cell layers suggests the presence of two populations of urothelial progenitor cells. Developmental Dynamics 243::988–998, 2014. © 2014 Wiley Periodicals, Inc.